The Effects of High Particulate Matter Levels on Platelet Recovery in Patients Receiving Prophylactic Platelet Transfusion - Hantrakool S; Sriwichai M; Shaengkhamnang B; Leetrakool N; Niprapan P; Kawichai S; Punnachet T; Hantrakun N; Piriyakhuntorn P; Rattanathammethee T; Chai-Adisaksopha C; Rattarittamrong E; et al. (Journal of Blood Medicine)
Sasinee Hantrakool,1 Maitree Sriwichai,2 Banphot Shaengkhamnang,2 Nipapan Leetrakool,2 Piangrawee Niprapan,1 Sawaeng Kawichai,3 Teerachat Punnachet,1 Nonthakorn Hantrakun,1 Pokpong Piriyakhuntorn,1 Thanawat Rattanathammethee,1 Chatree Chai-Adisaksopha,1 Ekarat Rattarittamrong,1 Adisak Tantiworawit,1 Lalita Norasetthada,1 Somdet Srichairatanakool4 1Division of Hematology, Department of Internal Medicine, Faculty of Medicine, Chiang Mai University, Chiang Mai, Thailand; 2Blood Bank Section, Faculty of Medicine, Chiang Mai University, Chiang Mai, Thailand; 3Research Institute for Health Sciences, Chiang Mai University, Chiang Mai, Thailand; 4Department of Biochemistry, Faculty of Medicine, Chiang Mai University, Chiang Mai, ThailandCorrespondence: Chatree Chai-Adisaksopha, Division of Hematology, Department of Internal Medicine, Faculty of Medicine, Chiang Mai University, Chiang Mai, Thailand, Tel +66 53 935488, Email chatree.chai@cmu.ac.thAim: Exposure to fine particulate matter, particularly PM2.5, has been associated with increased platelet activation and cardiovascular risks. However, its effect on platelet recovery after transfusion remains unclear.Purpose: This study aims to assess the influence of PM2.5 exposure on platelet recovery in patients with hematologic malignancies receiving prophylactic platelet transfusions.Patients and Methods: We conducted a cross-sectional study involving 66 patients with hematologic malignancies who developed chemotherapy-induced thrombocytopenia and received prophylactic platelet transfusions between January and December 2021. A total of 191 transfusion events were analyzed. Platelet increment and corrected count increment (CCI) were measured one hour post-transfusion. Transfusions were categorized based on mean PM2.5 levels one day prior to platelet collection: the control group (< 37.5 μg/m³) and the case group (≥ 37.5 μg/m³). Multivariate analyses were used to adjust for potential confounders.Results: No significant differences were observed in platelet increment (p = 0.128) or CCI (p = 0.828) between the PM2.5 exposure groups. Correlation analyses showed no significant association between PM2.5 levels and platelet increment (r = 0.0565, p = 0.437) or CCI (r = 0.0370, p = 0.614). These findings suggest that exposure to elevated PM2.5 levels one day before donation does not significantly impair platelet recovery.Conclusion: Short-term exposure to elevated PM2.5 levels does not significantly affect platelet recovery in patients receiving prophylactic platelet transfusions. These results provide important reassurance regarding the immediate effects of air pollution on transfusion outcomes, while highlighting the need for further research into potential long-term impacts.Keywords: platelet recovery, particulate matter, prophylactic platelet transfusion, hematologic malignancies, corrected count increment